2014
DOI: 10.2169/internalmedicine.53.1925
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis Caused by <i>Listeria monocytogenes</i> Forming a Pseudotumor

Abstract: A 73-year-old woman with breast cancer and metastasis under chemotherapy suffered from fever, pleural effusion and pericardial effusion. Despite the administration of treatment with cefozopran and prednisolone, the patient's fever relapsed. An electrocardiogram identified a new complete atrioventricular block and an echocardiogram revealed vegetation with an unusual pseudotumoral mass in the right atrium. Blood cultures grew Listeria monocytogenes. The patient was eventually diagnosed with right-sided infectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The involvement of listeriosis with AV block is yet to fully characterized in medical literature. During our review of published literature, we found only two case reports that reported AV block associated with listeriosis [16,17]. In the case report by Uehara et al [17], the patient was found to have a pseudotumor made up of L. monocytogenes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of listeriosis with AV block is yet to fully characterized in medical literature. During our review of published literature, we found only two case reports that reported AV block associated with listeriosis [16,17]. In the case report by Uehara et al [17], the patient was found to have a pseudotumor made up of L. monocytogenes .…”
Section: Discussionmentioning
confidence: 99%
“…During our review of published literature, we found only two case reports that reported AV block associated with listeriosis [16,17]. In the case report by Uehara et al [17], the patient was found to have a pseudotumor made up of L. monocytogenes . The patient subsequently required a pacemaker due to persistent symptomatic bradycardia despite receiving treatment with antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two reports of large right atrial masses consistent with tuberculomas on biopsy that completely resolved following 6 - 12 months of anti-tuberculous therapy [35, 36]. In addition, IP has also been reported in association with other infections including Listeria monocytogenes [37, 38] and Mycobacterium avium-intracellulare [39]. Primary cardiac tumors are often suspected by their appearance on imaging studies and the primary source of metastatic disease to the heart is usually obvious on review of history, examination, and laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“…About 60 % of listerial endocarditis is associated with valve dysfunction [ 3, 4 ], and patients with a prosthetic valve have a higher mortality rate than those with a native valve (41 and 31 %, respectively) [ 2, 3 ]. So far, approximately 80 cases of endocarditis due to Listeria monocytogenes have been reported in the literature [ 5 ]. Recurrent infection by Listeria monocytogenes occurs even more rarely.…”
Section: Introductionmentioning
confidence: 99%